Knowledge and attitude as determinants of practice of family planning among married men in Aleshinloye market, Ibadan (2019)
This study examined knowledge and attitude as determinants of practice of family planning among married men in Aleshinloye Market, Ibadan. Descriptive survey design method was used for the study. Purposive sampling method was used to select participants for the study while a single questionnaire tagged ‘ Knowledge and Attitude as determinants of Practice of Family Planning among Married Men Questionnaire (KA PFPMMQ) " was used to collect relevant data. Two null hypotheses were tested at 0.05 level of significance, using Pearson Moment Correlation. The study established that there was a significant relationship between knowledge and family planning practice among married men (r = .891, n— 150. P < .05). Also, it was also revealed that there was a significant relationship between attitude and family planning practice among married men at Aleshinloye market (r = .867. n- 150. P < .05! Based on the above findings the study recommends that government should create more awareness to educate the general populace as knowledge about the subject matter is important in it acceptance and change in attitude